The Washakie Letters of Willie Ottogary - Kreitzer, Matthew E. (Utah State University, University Libraries, 2000)
Writings by American Indians from the early twentieth century or earlier are rare. Willie Ottogary's letters have the distinction of being firsthand reports of an Indian community's ongoing social life by a community member and leader. The Northwestern Shoshone residing at the Washakie colony in northern Utah descended from survivors of the Bear River Massacre. Most had converted to the Mormon Church and remained in northern Utah rather than moving to a federal Indian reservation. For over twenty years, local newspapers in Utah and southern Idaho regularly published letters from Ottogary reporting happenings-personal milestones and health crises, comings and goings, social events, economic conditions and activities, efforts at political redress-at Washakie and other Shoshone communities in the intermountain West. Matthew Kreitzer compiled and edited the letters of Ottogary and added historical commentary and appendices, biographical data on individuals Ottogary mentioned, and eighty-five rare historical photographs. Written in a vernacular English and printed unedited in the newspapers, the letters describe a society in cultural transition and present Ottogary's distinctively Shoshone point of view on anything affecting his people. Thus, they provide an unusual picture of Shoshone life through a critical period, a time when many Indian communities reached a historical nadir. While the letters unflinchingly report the many difficulties and challenges the Shoshone faced, they portray a vital and dynamic society, whose members led full lives and actively pursued their own interests. Ottogary lobbied constantly for Shoshone rights, forging alliances with Shoshone throughout the region, visiting Washington D.C., advocating legislation, and participating in Goshute-Western Shoshone draft resistance during World War I.